Solar Steam Generation: Relationship Between the Material Properties and Pyroelectric‐Generating Performance of PZTs (Adv. Sustainable Syst. 3‐4/2017). (April 2017) - Yamanaka, Satoru; Kim, Juyoung; Nakajima, Akira; Katou, Takanori; Kim, Yoonho; Fukuda, Tatsuo; Yoshii, Kenji; Nishihata, Yasuo; Baba, Masaaki; Yamada, Noboru; Nakayama, Tadachika; Takeda, Masatoshi; et al.
Abstract : How can we convert exhaust heat from automobiles to renewable energy? In article number 1600020, Satoru Yamanaka, Yoonho Kim, and co‐workers present an innovative electro‐thermodynamic cycle as an answer. In pyroelectric applications, the relationship between the material properties and generating performance is investigated by utilizing the modified figure of merit for usage environment of automotive applications. Cover illustrator: Remi Tanaka.